The Bright Side of Life: Optimism and Risk of Dementia - Stenlund, Säde; Koga, Hayami K.; James, Peter; Farmer, Justin; McGrath, Colleen B.; Grodstein, Francine; Kubzansky, Laura D. (Wiley, 2026)
Background
Previous studies suggest that higher optimism is associated with better cognitive function and slower cognitive decline in aging. Using data from the Health and Retirement Study, a nationally representative sample of older U.S. adults, we examined whether optimism was associated with lower risk of developing dementia in different population groups and if associations were maintained after accounting for initial health status and other potential confounders and across multiple sensitivity analyses.
Methods
Optimism was measured using the validated Life Orientation Test-Revised in 9071 cognitively healthy individuals within 2 years of obtaining each person's first measure of cognitive function. Dementia was identified by an algorithm developed to perform well across major racial and ethnic groups, obtained at each of eight waves of data collection from 2006 to 2020. Cox proportional hazard models were used, and sensitivity analyses addressed major concerns such as reverse causation.
Results
We observed that a 1-standard deviation increase in optimism was associated with a lower hazard of developing dementia (hazard ratio = 0.85, 95% confidence interval 0.82–0.88), after adjusting for age, sex, race and ethnicity, education, depression, and major health conditions over follow-up ranging up to 14 years. When stratifying by race and ethnicity, we observed similar associations in the Non-Hispanic White and Black sub-populations. Associations did not substantially change when health behaviors were included in the models, when we removed the first 2 years of follow-up to mitigate concerns about potential reverse causation, or when we excluded individuals with the poorest mental health.
Conclusion
Higher optimism was associated with a lower incidence of dementia. These findings suggest a potential value of optimism in supporting healthy aging, which could be considered in future research on dementia prevention initiatives.